Karakteristik Fisik dan Organoleptik Crackers dengan Substitusi Tepung Pepaya Bangkok - Satiti Kawuri Putri; Ulyarti -; Mursyid -; Oktaviani Peranginangin (Universitas Pattimura, 2026)
Bangkok papaya flour (Carica papaya L.) has potential value in the food industry, particularly bakery products, as a substitute for wheat flour in cracker production. This study aimed to evaluate the use of Bangkok papaya flour as a wheat flour substitute on the physical and organoleptic characteristics of crackers. A Completely Randomized Design was applied with six levels of papaya flour substitution: 0%, 10%, 20%, 30%, 40%, and 50% with three replications. The physical parameters examined included hardness (texture), volume expansion, and color, while organoleptic assessment covered hedonic quality attributes (color and texture) as well as hedonic evaluation (taste and overall acceptance). The results showed that the addition of Bangkok papaya flour had a significant effect on texture, color parameters (L*, a*, b*), and all sensory aspects except volume expansion, which showed no significant difference. The best formulation was obtained at a 30% substitution level, with a hardness value of 81.36 gF, volume expansion of 3.3%, and color values of L* = 61.23, a* = 10.63, and b* = 27.03, visually classified as a slightly desaturated orange. Panelist scores for hedonic quality were 3.04 for color (slightly brownish) and 2.96 for texture (fairly crispy), 2.96 for taste (liked), and 3.20 for overall acceptance (relatively liked). These results indicate that Bangkok papaya flour has potential as a wheat flour substitute in cracker production, while also opening opportunities for developing functional, locally sourced cracker products that support food diversification and enhance the added value of the papaya commodity in Indonesia.